The Communication Behavior of German MPs on Twitter: Preaching to the Converted and Attacking Opponents. (September 2015) - Hegelich, Simon; Shahrezaye, Morteza
Abstract : What effect does the communication of politicians on Twitter have? Is it reinforcing existent ideologies because users get messages of politicians mostly from their own ideological cluster? Or is Twitter exposing the users to cross ideological content as well? We argue that both is the case. We show that politicians use the different communication channels. Twitter provides to distinguish between communication within their own ideological cluster in order to organize support and across these clusters to argue against their opponents. Considering German general elections as a case study, we present empirical tests that politicians—more than other politically interested users—use Twitter mostly to provide information but with significant differences between parties. We furthermore show that politicians use the whole spectrum of communication channels provided by Twitter. Finally, there is an empirical evidence of different qualities of the communicated content: measured by sentiment analysis the communication with members of the same party is less harsh than the communication with political rivals. This particular usage of communication on Twitter might lead to stronger polarization in political discourses.